Inconsistencies in Public Opinion of Body-Worn Cameras on Police: Transparency, Trust, and Improved Police–Citizen Relationships. (21st March 2017) - Sousa, William H.; Miethe, Terance D.; Sakiyama, Mari
Abstract: Given the national interest in equipping police with body-worn cameras (BWCs), it is important to consider public attitudes concerning the technology. This article draws on the results of a national survey of citizen opinions of BWCs. The survey includes items related to general support for BWCs, opinions on their potential advantages, and attitudes towards their potential consequences. Results indicate that while there is general support for BWCs on police, opinions vary on the capacity of BWCs to increase transparency of police work, improve trust in police, and better police–citizen relationships.